The disclosure practices of mosques in Singapore - Shareeza binti Anuar (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2015)
The deficiencies in reporting practices among the state mosques in Malaysia revealed that the responsibility to issue disclosure statements and reports, one of the significant tools of accountability, is not appropriately discharged. However. in Singapore. financial accounting and reporting is highly regulated which suggests that mosques in Singapore have sound financial reporting practices. In this light. this paper attempts to study one of Malaysia's neighbouring countries. Singapore, to learn of the disclosure practices of the mosques there. Thus. the main objective of this study is to examine the disclosure practices of mosques in Singapore. This study measured the extent of the information disclosed on the websites and financial statements of the mosques by using an adapted disclosure index. The findings of the study revealed that majority of the mosques have a website and comply with AMLA 1966 in having their financial statements displayed in the mosque. It was also found that the mosques could also voluntarily disclose non-financial information. This included the background of the mosques and their office bearers. list of sen·ices, and current and future programs. Further. information contained in the financial statements by the majority of the mosques conforms to the regulations and guidelines prescribed for them. although some inconsistencies were identified. The findings obtained from this study are expected to provide insight into the financial reporting of Singapore mosques and highlight the need to have a financial reporting framework for mosques in Malaysia. as well as other countries.